Peran Stakeholders dalam Implementasi Peraturan Tata Cara Pemberian izin Rumah Ibadat di Kota Bekasi - Theodorus Agustinus Hasiholan; Ari Subowo; Teuku Afrizal (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
The role of stakeholders is very decisive for implementing a policy, including the policy of granting permits to build houses of worship. Although in practice, in some cases, there are often conflicts between stakeholders. The Bekasi City Government has compiled Bekasi Mayor Regulation No. 107 of 2019 concerning Procedures for Granting Permits for the Construction of Houses of Worship. However, each stakeholder has not implemented these regulations properly, as evidenced by the frequent occurrence of conflicts. This study aims to analyze the role of stakeholders and identify the actors' understanding of the roles they carry out. This study uses the Theory of Power versus Interest from Bryson as the theoretical basis for this research. The methodology used in this research is descriptive qualitative, using secondary and primary data. The results showed that the Kesbangpol Agency was a Context Setter with the roles of Policy Creator, Facilitator, and Coordinator. Bekasi City FKUB is Key Player who have the roles of coordinator, Facilitator, and implementer. The Regional Office of the Ministry of Religion of Bekasi City is a key player who has the Policy Creator, Facilitator, and Implementer role. The Social Welfare Agency for the Regional Secretariat of the city of Bekasi is a Context Setter with the roles of Facilitator and Implementer. Sub-Districts is a Crowd with the role of Facilitator. Urban Village is a Crowd with the role of Facilitator. Regarding understanding, there are two supporting factors in granting permits to build houses of worship in Bekasi City, namely value and communication. Meanwhile, two other inhibiting factors are communication and policy sources.